Developing Character Through 'Seni Dendang' Instructional Materials in Elementary Schools to Enhance the Pancasila Student Profile - Tarmizi, Pebrian; Danim, Sudarwan; Wardana, Rendy Wikrama (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to develop feasible and practical ethnopedagogy-based Seni Dendang teaching materials to integrate character values at SDN South Bengkulu. Using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, this research involved six expert validators (material, language, and media) and limited trials with teachers and fifth-grade students. Data were collected through interviews, documentation, and Likert-scale questionnaires, then analyzed qualitatively and quantitatively using Aiken’s V index and the percentage agreement formula. Validation results showed a very high level of feasibility, with average scores of 0.86 from material experts (Highly Feasible), 0.83 from language experts (Highly Feasible), and 0.86 from media experts (Highly Feasible), with expert agreement reliability exceeding 81% (Very Strong). Field trial results demonstrated extraordinary practicality, with student responses reaching 97.71% and teacher responses at 98.33%. This study concludes that these character-based Seni Dendang teaching materials are effective and practical for use as a learning resource to enhance student character while systematically preserving local cultural identity in elementary schools. The significance of this research lies in its dual impact: practically, it provides a concrete solution to the deficit of contextually relevant learning resources by utilizing local wisdom as an active instrument for character building. Theoretically, it enriches the field of Educational Technology by demonstrating the successful integration of ethnopedagogy within the ADDIE framework to strengthen the national character values aligned with the Merdeka Belajar curriculum.